ANALISIS PENDAPATAN CV. RAHMAT DI ERA PANDEMIC COVID-19 - Nurmiati, Nurmiati; Nurwahyuni, Nurwahyuni; Ilham, Ilham; Lubis, Bastian (Universitas Patria Artha, 2022)
This study aims to determine and analyze the impact of Covid-19 on the income of Tent And Decoration at CV. Grace. This research is a quantitative descriptive research using frequency distribution data analysis. The results showed that the covid-19 pandemic resulted in Tent And Decoration income at CV. Rachmat experienced a very significant decline where the pattern of customers and the number of customers experienced a very drastic change as well as related to the profits obtained even though the rental prices set tended to be competitive.